Neoplasic gastrojejunal fistulas - Praderi, Raúl (Cirugía del Uruguay, 1972)
The study deals with two cases of fistulized gastrie cancer in the duodenojejunal angle. One of the patients had undergone. 14 years previously subtotal colectomy due to cancer und had neither mesocolon nor transverse colon. In the other case the tumor had also invaded the colon, which it infiltrated and occluded. In the first case there was also massive digestive hemorrhage. Intrahemorrhagic gastrectomy was performed without success. In the second case the gastric tumor had perforated into the peritoneum. The perforation was made into a gastrostomy and transversal colostomy was performed as treatment foc the occlusion of the large intestine.